“For everything to function, people need water” - CGIAR (CGIAR System Organization, 2023)
Meet NEXUS Gains’ partners in the Shashe sub-basin The Shashe River originates in Botswana and forms part of the country’s long border with Zimbabwe, yet for much of the year, few would recognize this landmark as a river. Highly ephemeral, the Shashe is more commonly a dry, sandy channel. On the occasions that the rain replenishes it, the Shashe flows into the Limpopo River. In this arid landscape, efficient, well-designed water storage is crucial to ensure food and water security, secure livelihoods, and build climate resilience. The CGIAR initiative on NEXUS Gains is working in the Shashe sub-basin to bring together stakeholders across sectors, from both banks of the river, to encourage collaboration, knowledge-sharing, and innovation.